The Clinical Spectrum and Therapeutic Management of Hypocomplementemic Urticarial Vasculitis: Data From a French Nationwide Study of Fifty‐Seven Patients. Issue 2 (February 2015) - Jachiet, Marie; Flageul, Béatrice; Deroux, Alban; Le Quellec, Alain; Maurier, François; Cordoliani, Florence; Godmer, Pascal; Abasq, Claire; Astudillo, Leonardo; Belenotti, Pauline; Bessis, Didier; Bigot, Adrien; et al.
<x xml:space="preserve">Abstract</x> Objective Hypocomplementemic urticarial vasculitis (HUV) is an uncommon vasculitis of unknown etiology that is rarely described in the literature. We undertook this study to analyze the clinical spectrum and the therapeutic management of patients with HUV. Methods We conducted a French nationwide retrospective study that included 57 patients with chronic urticaria, histologic leukocytoclastic vasculitis, and hypocomplementemia. We assessed clinical and laboratory data and evaluated the patients' cutaneous and immunologic responses to therapy. We evaluated treatment efficacy by measuring the time to treatment failure. Results Urticarial lesions were typically more pruritic than painful and were associated with angioedema in 51% of patients, purpura in 35%, and livedo reticularis in 14%. Extracutaneous manifestations included constitutional symptoms (in 56% of patients) as well as musculoskeletal involvement (in 82%), ocular involvement (in 56%), pulmonary involvement (in 19%), gastrointestinal involvement (in 18%), and kidney involvement (in 14%). Patients with HUV typically presented with low C1q levels and normal C1 inhibitor levels, in association with anti‐C1q antibodies in 55% of patients. Hydroxychloroquine or colchicine seemed to be as effective as corticosteroids as first‐line therapy. In patients with relapsing and/or refractory disease, rates of cutaneous and immunologic response to therapy seemed to be higher with conventional immunosuppressive agents, in particular, azathioprine, mycophenolate mofetil, or cyclophosphamide, while a rituximab‐based regimen tended to have higher efficacy. Finally, a cutaneous response to therapy was strongly associated with an immunologic response to therapy. Conclusion HUV represents an uncommon systemic and relapsing vasculitis with various manifestations, mainly, musculoskeletal and ocular involvement associated with anti‐C1q antibodies, which were found in approximately half of the patients. The best strategy for treating HUV has yet to be defined.